A Note on the Calendar of the Liber Floridus. (2015) - Ivanov, Sergey
Abstract : This paper examines some hitherto unconsidered marginal notes in the calendar of the Liber Floridus (year 1121) and establishes their link with the popular medieval text on the twelve fasting Fridays. The calendrical form of representation makes this information appear side by side with a list of events supposed to have happened on 25 March — a possible starting point for the development of a longer textual version contaminating the list of the twelve Fridays and the list of Friday events.